Click Chemistry for Analysis of Cell Proliferation in Flow Cytometry. Issue 1 (13th February 2018) - Clarke, Scott T.; Calderon, Veronica; Bradford, Jolene A.
Abstract: The measurement of cellular proliferation is fundamental to the assessment of cellular health, genotoxicity, and the evaluation of drug efficacy. Labeling, detection, and quantification of cells in the synthesis phase of cell cycle progression are not only important for characterizing basic biology, but also in defining cellular responses to drug treatments. Changes in DNA replication during S‐phase can provide valuable insights into mechanisms of cell growth, cell cycle kinetics, and cytotoxicity. A common method for detection of cell proliferation is the incorporation of a thymidine analog during DNA synthesis. This chapter presents a pulse labeling method using the thymidine analog, 5‐ethynyl‐2′‐deoxyuridine (EdU), with subsequent detection by click chemistry. EdU detection using click chemistry is bio‐orthogonal to most living systems and does not non‐specifically label other biomolecules. Live cells are first pulsed with EdU. After antibody labeling cell surface markers, fixation, and permeabilization, the incorporated EdU is covalently labeled using click chemistry thereby identifying proliferating cells. Improvements in click chemistry allow for labeling in the presence of fluorescent proteins and phycobiliproteins without quenching due to copper. Measuring DNA replication during cell cycle progression has cell health applications in flow cytometry, fluorescence microscopy, and high content imaging. This protocol has been developed and optimized for research use only and is not suitable for use in diagnostic procedures. © 2017 by John Wiley & Sons, Inc.